Evaluating the freezing impact on the proximate composition of immature cowpea (Vigna unguiculata L.) pods: classical versus spectroscopic approaches. (12th April 2017) - Machado, Nelson; Oppolzer, David; Ramos, Ana; Ferreira, Luis; Rosa, Eduardo AS; Rodrigues, Miguel; Domínguez‐Perles, Raúl; Barros, Ana IRNA
Abstract: BACKGROUND: Freezing represents a common conservation practice regarding vegetal foodstuffs. Since compositional features need to be monitored during storage, the development of rapid monitoring tools suitable for assessing nutritional characteristics arises as a pertinent issue. In this study, cowpea ( Vigna unguiculata L.) pods, both fresh and after 6 and 9 months of freezing at −18 °C, were evaluated by high‐performance liquid chromatography for their content of protein as well as of essential and nonessential amino acids, while their Fourier transform infrared spectra in the mid infrared (MIR) and near infrared (NIR) ranges were concomitantly registered to assess the feasibility of this approach for the traceability of these frozen matrices. RESULTS: For the NIR interval, the application of the 1st derivative to the spectral data retrieved the best results, while for lower concentrations the application of the Savitzky–Golay algorithm was indispensable to achieve quantification models for the amino acids. MIR is also suitable for this purpose, though being unable to quantify amino acids with concentrations below 0.07 mmol g −1 dry weight, irrespective of the data treatment used. CONCLUSIONS: The spectroscopic approach constitutes a methodology suitable for monitoring the impact of freezing on the nutritional properties of cowpea pods, allowing accurate quantification of the protein and amino acid contents, while NIR displayed better performance. © 2017 Society of Chemical Industry